2020
DOI: 10.1016/j.techfore.2020.120337
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial entry: The role of social media

Abstract: Despite the exponential growth of social media use, whether and how social media use may affect entrepreneurial entry remains a key research gap. In this study we examine whether individuals’ social media use influences their entrepreneurial entry. Drawing on social network theory, we argue that social media use allows individuals to obtain valuable social capital, as indicated by their offline social network, which increases their entrepreneurial entry. We further posit the relationship between social media u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…Current literature [e.g. 8,43] has reported that digitalisation efficiently assists entrepreneurs in acquiring different knowledge and information to progress the sustainability of their venture and the growth of the business, such as customer information or market asymmetries, and in mobilising resources. Easton and Araujo [18] pointed out that with the aid of digital advancement and digital technology, entrepreneurs can overcome the scarcity of resources (finance, time, effort, human resources) and yet still maintain efficient forms of communication and access the amount of information needed for their business.…”
Section: Digitalisation and Entrepreneurial Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature [e.g. 8,43] has reported that digitalisation efficiently assists entrepreneurs in acquiring different knowledge and information to progress the sustainability of their venture and the growth of the business, such as customer information or market asymmetries, and in mobilising resources. Easton and Araujo [18] pointed out that with the aid of digital advancement and digital technology, entrepreneurs can overcome the scarcity of resources (finance, time, effort, human resources) and yet still maintain efficient forms of communication and access the amount of information needed for their business.…”
Section: Digitalisation and Entrepreneurial Networkmentioning
confidence: 99%
“…Easton and Araujo [18] pointed out that with the aid of digital advancement and digital technology, entrepreneurs can overcome the scarcity of resources (finance, time, effort, human resources) and yet still maintain efficient forms of communication and access the amount of information needed for their business. Digitalisation provides entrepreneurs with sufficient tools to efficiently manage their online relationships and reinforce their offline relationships beyond geographical proximity and at an efficient cost-effectiveness [43][44]. In addition, digitalisation leads to an increase in digital information and the ability to access information in turn structures, shapes and influences our modern market [45].…”
Section: Digitalisation and Entrepreneurial Networkmentioning
confidence: 99%
“…For example, enterprises from emerging economies tend to nurture their domestic market capabilities to create a foundation before embarking on internationalization (Li Sun, 2009). Furthermore, other entrepreneurship research finds that the capability to utilize online social-network capitals impacts individuals' entrepreneurial entry (Wang et al, 2020).…”
Section: Categorizing Substantive Capabilitiesmentioning
confidence: 99%
“…Finally, the impact of social media on individuals' entrepreneurial entry was also examined.This studies refer to individual entrepreneurships which, by size, do not use the information systems of more structured companies. For example, a research [90] in this field was supported by a sample of adults in China. The study reports that although social media is dominated by weak ties and substantial noisy information (sometimes even false information), the results reveal that people with greater use of social media tend to conduct an entrepreneurial entry.…”
Section: Social Media and Firmsmentioning
confidence: 99%